Factors related to anxiety and depression in HIV patients from a public hospital - Tapullima-Mori, Calixto (2022)
Objectives: To analyze the factors related to anxiety and depression in patients with HIV in a Public Hospital. Methods: The study was cross-sectional, non-experimental, and basic in design, involving 230 patients, and the Zung Depression and Anxiety Scale was applied. Results: Of the participants evaluated, 41.3 % were between 18 and 25 years old predominantly, with LGTBI sexual orientation 40.4%; of these, 53.9% do not know the current viral load and do not follow treatment, while the level of anxiety and depression in PVV was 48.3% and 47.8%. Conclusions: Sexual orientation, ignorance of viral load, follow-up of treatment and degree of education are the factors of greatest relationship with anxiety and depression in PVV, although age less than or equal to 25 years triggers a higher prevalence of these symptoms, there was no statistical difference with other groups.